Indigenous and decolonial futures: Indigenous Protected and Conserved Areas as potential pathways of reconciliation - Townsend, Justine; Roth, Robin (Frontiers in Human Dynamics, 2023)
Crown governments, the conservation sector, academics, and some Indigenous governments, communities, and organizations are framing Indigenous Protected and Conserved Areas (IPCAs)—a newly recognized form of Indigenous-led conservation in Canada—as advancing reconciliation with Indigenous Peoples. Yet it is often unclear what is being, or could be, reconciled through IPCAs. While highly diverse, IPCAs are advanced by Indigenous Nations, governments, and communities who protect them, with or without partners, according to their Indigenous knowledge, legal, and governance systems. IPCAs may be expressions of “generative refusal,” visions of Indigenous futures, and commitments to uphold responsibilities to the lands, waters, and past and future generations. IPCAs refuse settler colonial ontologies including the expectation of ongoing white settler privilege, which relies on the continued appropriation of lands and resources. By examining the practical, relational, and systemic challenges Indigenous Nations advancing IPCAs encounter, we discuss opportunities for Crown governments and the conservation sector to cultivate decolonial responses. Indigenous Nations advancing IPCAs may face challenges with resource extraction, laws and legislation, financing, relationships and capacity, and jurisdiction and governance. We contend that IPCAs could be pathways of reconciliation if Crown governments and the conservation sector support IPCAs in ways consistent with the recommendations of Indigenous leaders. This requires dismantling the roadblocks arising from settler ontologies and institutions that impede IPCA establishment and ongoing stewardship. Thus, not only could Indigenous futures be advanced, we might also cultivate decolonial futures in which all peoples and species can thrive.